(untitled) (Medicine Today, 2025)
Introduction: Breast cancer is a significant public health concern worldwide and has a significant impact on individuals, families, and society. While progress has been made in the diagnosis, treatment, and prevention of breast cancer, there is still much to be learned about the disease and its impact on patients. The objective of the study was to find out the socio-demographic characteristics of breast cancer among women in a selected cancer specialized hospital in Dhaka city. Materials and Methods: This cross-sectional Study was carried out among 108 patients attending at the department of Oncology at Delta Medical College Hospital; Dhaka for the treatment of breast cancer within the defined period from January 2022 to December 2022. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. Result: Majority of the breast cancer patients (32.41%) were within the age range of 50-59 and 40-49 years. The most common weight for the breast cancer patients was in the range of 40-50 kg with frequency of 43(39.81%). Most of the respondents have come from urban areas with a frequency of 63 (58.33%). Most of the breast cancer patients were housewives (n=61, 56.48%) followed by service holders (n= 30, 27.78%). Most of the patients (n=94, 87%) were married. Most of the women were Muslim (87%). Family history was positive for 61 patients (56.48%). Out of 108 patients, 63 of the respondents had diabetes (58.3%). Out of the 108 respondents having breast cancers, 61 (56.5%) reported not using contraceptive pills, whereas 47 (43.5%) used contraceptive pills. Only 22.22% breast cancer patients used hormone replacement therapy. Out of 108 breast cancer patients, having exposure to X-ray was with frequency 44 (40.74%) and having no X-ray exposure was with frequency 64 (59.26%). Most of the breast cancer patients (n=70, 64.81%) were prone to betel-nut chewing habit. The highest frequency was 58 (53.7%) who were having daily 2 cups of tea which was followed by 3 cups of tea 25 (23.15%). Most of the respondents (n= 67, 62.04%) were prone to taking added salt consumption. 48 (44.44%) of the respondents had red meat for more than one time in a week. For the breast cancer patients, having no alcohol consumption was the higher number (n=61, 56.48%), whereas the alcohol consumption number was 47 (43.52%). Conclusion: In our study breast carcinoma was more common within the age range of 50-59 and 40-49 years. Regular screening of this age group through mammography will helps to early detection of breast carcinoma. Medicine Today 2025, Vol.37 (2): 189-192